Metacognitive Awareness and Numerical Proficiency of Bachelor of Secondary Education Major in Mathematics - Derequito, Karen G.; Ericka Mea P. Laporca; April Joy C. Verallo; Norberto Jr M. Ferrer (Researchparks Publishing, 2025)
This study investigates the relationship between metacognitive awareness and numerical proficiency among Bachelor of Secondary Education (BSED) students majoring in Mathematics at the University of Cabuyao during the academic year 2024–2025. Employing a descriptive-correlational research design, the study assessed metacognitive awareness in terms of knowledge (declarative, procedural, and conditional) and regulation (planning, monitoring, and evaluating), alongside numerical proficiency, which encompassed numerical literacy, skills, and aptitude. Data were collected from 103 respondents using validated researcher-made instruments and analyzed using statistical methods, including Spearman’s Rho. Findings revealed that respondents demonstrated high levels of metacognitive awareness across all dimensions, with notable variability in individual performance. Similarly, numerical proficiency was predominantly rated as high, with numerical aptitude achieving the highest scores. A significant positive correlation was identified between metacognitive awareness and numerical proficiency, underscoring the critical role of metacognitive skills in enhancing mathematical competencies. The study highlights the importance of fostering metacognitive practices to improve problem-solving, critical thinking, and adaptability in mathematics education. These findings provide valuable insights for educators, curriculum developers, and policymakers in designing targeted interventions to enhance metacognitive and numerical skills among pre-service mathematics teachers. By addressing individual differences and promoting reflective learning strategies, this research contributes to the development of competent and adaptive mathematics educators capable of meeting the demands of 21st-century education.